The colonization of a new area in the first six months following ‘same-day’ free release translocation of black rhinos in Kenya - Patton, Felix; Mulama, M.S.; Mutisya, Samuel; Campbell, P.E. (Pachyderm, 2010)
In February 2007, 27 black rhinos (Diceros bicornis) were translocated to an area in the Ol Pejeta Conservancy in central Kenya that contained no resident population. The rhinos were ‘free’ released on the same day of their capture at 11 sites spread throughout the new area in order to minimize future conflict. Free release had not been tried on such a scale in Kenya. Following release, the rhinos were closely monitored through radio tracking and direct observation to record their movements and how quickly they settled in their new environment. In the first six days after release, 17 of the 27 rhinos remained close to their release sites while one individual travelled 35.1 km. All rhinos bar one settled within six months of release; 16 had settled within 25 days. The rhinos moved on average 7.69 km from their release sites with 14.57 km the maximum distance moved. With no reported fights between conspecifics and the ease of settling of the rhinos in their new location, the results obtained from the free release translocation used at Ol Pejeta Conservancy show it to be a useful alternative approach to future rhino translocations. En février 2007, 27 rhinocéros noirs (Diceros bicornis) ont été transférés dans une région de la Conservation d’Ol Pejeta au centre du Kenya qui n’avait pas de population résidante. Les rhinocéros ont été relâchés « libres » le même jour de leur capture dans 11 sites répartis dans la nouvelle aire pour minimiser de futurs conflits. Le relâchement libre n’avait pas été essayé à une telle échelle au Kenya. Suivant le relâchement, les rhinocéros étaient suivis attentivement à travers un dépistage par radio et une observation directe pour enregistrer leurs mouvements et constater la rapidité avec laquelle ils s’établissaient dans leur nouvel environnement. Dans les six premiers jours après le relâchement, 17 des 27 rhinocéros sont restés près de leur site de relâchement tandis qu’un individu a voyagé 35,1 km. Tous les rhinocéros à l’exception d’un seul s’étaient établis endéans six mois de leur relâchement; 16 s’étaient établis dans 25 jours. Les rhinocéros se sont déplacés en moyenne de 7,69 km de leur site de relâchement avec une distance maximale de 14,57 km de déplacement. Etant donné l’absence de combats rapportés entre congénères et la facilité d’établissement des rhinocéros dans leur nouvel site, les résultats obtenus de la translocation de relâchement libre utilisée dans la Conservation d’Ol Pejeta montre que c’est une autre approche utile pour les translocations futures des rhinocéros.